IMPACT OF PROFESSIONAL AND CHRONOLOGICAL AGE ON THE PRODUCTIVITY OF SCIENTISTS IN ENGINEERING SCIENCE LABORATORIES OF CSIR - Gupta, B.M.; Kumar, Suresh; Khanna, H.K.; Amla, T.K. (Malaysian Journal of Library and Information Science, 1999)
Examines the two types of research output of scientists varying in chronological and professional age of engineering sciences in India. The mathematical models of aging derived from the earlier studies have been tested in the two types of scientific and technical output in order to determine the linear and non-linear trends and the productivity rate for each interval.